The fragility of identity in the age of manufacture - Lazaro, Elaine M. (2016)
This essay begins with a discussion of how globalization poses a threat to identity. To support this claim, the second part reflects on the pathologies of the city, as characterized by Paul Ricoeur, with a particular emphasis on memory.
Keywords: Cultural identity; Globalization -- Social aspects